Ethical challenges in hospital duty: Nepalese nurses’ lived experience - Sharma, Muna; Sharma, Kalpana (Journal of Chitwan Medical College, 2020)
Background: Nursing is ethically grounded profession. Nurses work in proximity with patients where they may encounter ethical problems too. However, little is known about the ethical challenge of nurses working in Nepal. Therefore, this study was undertaken to explore lived experience with ethical challenges among nurses working in government hospitals of Kathmandu, Nepal. Methods: Qualitative phenomenological design was carried out among nurses working in the five government hospitals of Kathmandu, Nepal. Twelve nurses who had greater than 5 years of work experience in patient care were selected purposively for the study. Data was collected through face to face interview method using in-depth interview guideline. All interviews were recorded in a digital voice recorder. The collected verbatim was transcribed and analyzed thematically. Results: All nurses experienced ethical challenges and perceived stress from those challenging situations. Three main themes derived from the participants’ experiences of ethical challenges were: errors in patient management; justice to the patient; burn out from duty. Nurses found inappropriate service to the patients, limited access of treatment and care to the patients, errors in procedure, autonomy and confidentiality issues, compromised respect and dignity of patients. When nurses found stressful working situation and conflicting legal and moral obligations, they felt burnout that leads to compromised quality of patients care. Conclusions: Nurses experience different ethically challenging situations in their duties. Experiences of these challenging situations are stressful and it affects nurses’ ability to deliver quality service. Hence, attention should be given to address ethical challenges of nurses.